Temporal and spatial distribution characteristics of stratospheric aerosols over xinjiang region based on CALIPSO spaceborne lidar observation - ZiWei, Li; Xiangling, Tang (Frontiers in Earth Science, 2022)
This paper presents an analysis of the temporal and spatial distribution characteristics of stratospheric aerosol over Xinjiang region using the level-3 product of stratospheric aerosol profile acquired by CALIPSO spaceborne lidar from 2007 to 2018. The findings are: Firstly, the optical depth of stratospheric aerosol over Xinjiang is considerably higher in spring (0.0006) and summer (0.0009), than in autumn (0.0003) and winter (0.0002). This is most likely caused by the seasonal difference in the intensity of convective activities in the stratosphere alone as well as atmospheric dynamics (such as strong winds) induced exchange of aerosols between the troposphere and the stratosphere in the studied area. Secondly, the backscattering ratio of stratospheric aerosol particles decreases with the increase of altitude, with the bottom of the stratosphere as the main contributor of the optical depth. Thirdly, for latitudinal distribution (35°-50° north latitude), the backscattering ratio gradually increases from south to north, with an average value that reaches 0.0013×10-3 km-1sr-1 at maximum in May and 0.0003×10-3 km-1 sr-1 at minimum in January, October and December.